Note on Income Taxation and Occupational Choice - Eytan Sheshinski (Center for Economic Studies and ifo Institute (CESifo), 2003)
With varying aptitudes in different occupations, individuals typically maximize income by specializing in one occupation which promises the highest income. Due to numerous labor market imperfections and uncertainties, the choice of best occupation is accomplished with only partial success. We demonstrate that an income tax that reduces after-tax income differentials across occupations tends to exacerbate the errors of choice made by individuals. Following a model proposed by Tinbergen (1951) and developed by Houthakker (1974), we use Luce's (1959) multinominal logit approach to evaluate the magnitude of the distortions due to errors in occupational choice caused by income taxation. In an example, we show that the deadweight loss can be as high as a third of total income.
Keywords: 330; distribution of aptitudes; size distribution of income; logit model